Effect of Crop Establishment Method and Nutrient Management on Yield and Yield Attributes of Short Duration T. Aman Rice - Nahar, L; Sarker, ABS; Mahbub, MM; Akter, R (Bangladesh Agronomy Journal, 2018)
A field trial was conducted at Agronomy Farm of Bangladesh Rice Research Institute to find out the effect of crop establishment method and nutrient management on yield performance of BRRI developed short-duration Aman rice var. BRRI dhan62 during July to October 2016. The trial comprised of four crop establishment methods viz., M1 = BRRI recommended puddle transplanting, M2 = System of rice intensification (SRI) method (9-days old seedling transplantation), M3 = Sprouted seed in line sowing and M4 = Sprouted seed in broadcasting and three nutrient management levels viz.,N1 = BRRI recommended nutrient management, N2 = Soil test-based nutrient management, N3 = Control. The study was conducted in a factorial Randomized Complete Block Design with three replications. The result showed that planting methods had significant effects on the yield of rice. The SRI method along with BRRI recommended fertilizer dose produced the maximum grain yield of 4.49 t ha-1 which was statistically similar with that produced in SRI method day- and soil test-based nutrient management combination. The highest gross margin (Tk. 36,308.00 ha-1) and cost benefit ratio (2.06) were observed in direct seeding of sprouted seed in line sowing method along with BRRI recommended fertilizer dose. So, direct seeding of sprouted seed in line could be a suitable planting method due to reduction of 26.0% production cost associated with seedling raising and transplanting operations. Bangladesh Agron. J. 2018, 21(1): 117-123